Trajectory planning for smooth motion of a surgical robot - Vui, Lee Jer; Taha, Zahari; Yap, Hwa Jen; Iskandar, Iskandar; Ali, Mohamed Razif Mohamed (Penerbit Universiti Sains Malaysia, 2004)
Surgical robotics offers a number of attractive features. It can be used to filter out surgeon’s hand tremor, enhance a surgeon’s motions and perform microscale movements that are otherwise impossible for a human to perform. Because the control workstation can be located away from the surgical theatre, it enables a surgeon to manipulate an instrument during radiation or chemical treatment, via a robot, distancing the surgeon from harmful effects. Computer aided surgical simulation via virtual reality improves the process of surgical training. New surgeons could ultimately be trained entirely by computer simulation. Furthermore, the virtual environments provide an environment where there is no risk to a patient.